Cueing-assisted gamified augmented-reality gait-and-balance rehabilitation at home for people with Parkinson’s disease: protocol of a pragmatic randomized controlled trial implemented in the clinical pathway - Geerse, Daphne J.; Hoogendoorn, Eva M.; van Doorn, Pieter F.; van Bergem, Jara S.; van Dam, Annejet T.; Hardeman, Lotte E. S.; Roerdink, Melvyn (Frontiers in Neurology, 2025)
BackgroundPhysiotherapy in the clinic is highly recommended for improving gait, balance, and fall risk in people with Parkinson’s disease. In addition, technology may help boost unsupervised exercise hours at home. Strolll is an augmented-reality (AR) neurorehabilitation platform for delivering gait-and-balance exercises onto AR glasses that can be performed under direct supervision of the therapist in the clinic, but also independently at home. Strolll AR also has the option to integrate AR cueing in gait-and-balance exercises to assist people with more severe mobility impairments in performing the exercises. The objective of this pragmatic randomized controlled trial (RCT) on Strolll AR is to examine its clinical feasibility and effectiveness for improving indicators of gait, balance, and falls risk. A secondary objective is to evaluate procedures for tailoring assistive AR cues.MethodsA total of 100 people with Parkinson’s disease (Hoehn and Yahr stages 1–3) with gait and/or balance impairments will participate in this study. This study is a pragmatic RCT in which all participants follow the same procedure. After a baseline assessment (T0), participants will start with a 6-week usual care control period, followed by a midterm assessment (T1). Subsequently, participants will undergo 2 weeks of in-clinic familiarization with Strolll AR. Then, participants will start with the 6-week Strolll AR intervention at home, followed by a final in-clinic assessment (T2). The primary study parameters are feasibility (i.e., safety, adherence, performance, and user experience) and effectiveness for improving indicators of gait, balance, and falls risk. For the statistical analyses on effectiveness, participants will be allocated to control (using T0-T1 change data) or intervention (using T1-T2 change data) groups using multiple (n = 20) randomizations. Recruitment started in May 2024 and the last T2 assessment is expected in February 2025.DiscussionThe design of this particular pragmatic RCT will demonstrate feasibility and effectiveness in a real-world setting and in a representative population. Strolll AR may facilitate the transition from supervised care in the clinic to independent care at home, providing a platform for delivering individualized treatment, assisted with AR cues when deemed beneficial, for improving gait, balance, and falls risk in people with Parkinson’s disease.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT06590987